2012
DOI: 10.1177/0044118x12451276
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Stage-Environment Fit in Middle and High School

Abstract: This mixed-methods longitudinal project investigates the association between student perceptions of their schools and themselves. Findings from the first two waves of data analysis with 894 middle and high school students in a midsized Great Lakes city reveal similarities and differences between the grade levels (7th–10th) and their perceptions of their schools. Although 7th-grade students enter middle school with the most positive feelings about their schools, they lose this feeling of euphoria by the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…Second, our findings show that in both the United States and Korea, TSMC positively mediates the relationship between PDME and the perceptions of school climate. In other words, the benefits of participating in PDME go beyond TSMC to enhance school climate, which has been shown to have positive effects on students' behavioral, social, and academic outcomes (Booth & Gerard, 2014;Konold et al, 2018;Lewis et al, 2017). This aligns with Judith Warren Little's (1993) argument where she stated, "The most promising of these efforts [professional development] engage teachers collectively in studying classroom practices in ways that sometimes lead to more systemic changes at the school level" (p. 131).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Second, our findings show that in both the United States and Korea, TSMC positively mediates the relationship between PDME and the perceptions of school climate. In other words, the benefits of participating in PDME go beyond TSMC to enhance school climate, which has been shown to have positive effects on students' behavioral, social, and academic outcomes (Booth & Gerard, 2014;Konold et al, 2018;Lewis et al, 2017). This aligns with Judith Warren Little's (1993) argument where she stated, "The most promising of these efforts [professional development] engage teachers collectively in studying classroom practices in ways that sometimes lead to more systemic changes at the school level" (p. 131).…”
Section: Discussionmentioning
confidence: 87%
“…The positive impacts of school climate have been well documented. For instance, research found that school climate had a positive impact on academic engagement and achievement (Konold et al, 2018), self-esteem (Booth & Gerard, 2014), and emotional health (Lewis et al, 2017). Research also showed that teachers' perceptions of school climate were positively associated with reducing disruptive behavior (Mitchell et al, 2010) and improving academic achievement (Bear et al, 2014;B.…”
Section: Pdme Tsmc and School Climatementioning
confidence: 99%
“…This provides a basis for determining trajectories of change across school years, but does not address important changes that may occur within school years. Contextual and developmental changes that occur during middle school highlight the need to examine changes not only across grades, but also within each grade (Booth & Gerard, 2014). As Collins (2006) noted, because change that occurs between observations is not observed, frequent observations are required when change is rapid.…”
mentioning
confidence: 99%
“…This age group is critical for understanding the development of social goals given contextual and development changes during adolescence. Similar to changes that occur during the transition from elementary to middle school (e.g., Midgley, Anderman, & Hicks, 1995;Wang & Holcombe, 2010), the transition from middle to high school brings substantial school context changes such as multiple teachers throughout the day (typically more so than in middle school), exposure to a greater number of peers, and a less intimate environment (Booth & Gerard, 2012;Eccles & Roeser, 2011;Ganeson & Ehrich, 2009). Furthermore, developmental changes in interpersonal relationships arise during late adolescence, for example, by ages 16-18, students report that friend support exceeds both teacher and parent support (Bokhorst, Sumter, & Westenberg, 2010).…”
Section: Current Studymentioning
confidence: 99%
“…As we predicted from other longitudinal studies (e.g., Archambault et al, 2010), younger students who have just transitioned to high school reported less stability in their goals across the year, while those who have had a year or more to adjust to the transition to high school were more stable. A possible explanation for this post-transition fluctuation of social goals might be explained by a temporary boost in positive perceptions of school climate that occurs right after transitions to new school environments (Booth & Gerard, 2012). Students might perceive this transition as an opportunity to improve social networks and therefore emphasize social development goals.…”
Section: The Role Of Individual Background Variablesmentioning
confidence: 99%